Freudian Dynamics in Nonsense Poetry “The Walus and the Carpenter” - Betharia Sembiring Pandia (Akademi Komunitas Negeri Putra Sang Fajar Blitar, 2026)
This study examined the psyches components identified in Lewis Carroll's poetry using Sigmund Freud's human psyches theory. Drawing upon Sigmund Freud’s theory of the human psyche particularly the concepts of the id, ego, and superego, this research investigated how unconscious desires, internal conflicts, and repressed impulses are reflected in Carroll’s poetic language and characterization through the aspects of personality in literary work. In addition to this, the dynamics among the aspects were also explored. This study applied descriptive qualitative research design. The source of the data in this study was the poetry’s online record, especially Lewis Carroll’s nonsense poetry entitled The Walrus and the Carpenter. As the data, phrases and sentences were taken to be analyzed according to the Freudian’s psychoanalysis theory. The data were analysed by using a psychological approach based on Sigmund Freud’s psychoanalytical theory. The analysis began with reading on the poem, identifying words, phrases, and sentences in each stanza that reflected psychological aspects from all characters, namely the Walrus, Carpenter and the Oysters. Freud’s category and concept of id, ego, and superego were used as the labels for all identified psychological events within the poetry. After the classification, the data was interpreted by using Freud’s theory to determine: (1) which personality structure is dominant in each character; (2) the movement or dynamics of the psychological structure among id, ego, and superego to create a sense of coherent narrative in a nonsense poetry entitled The Walrus and the Carpenter. The analysis revealed that ego was the most dominant element of psychological structure. The ego was used as the strategy to weaken the character the Walrus in order to achieve his id; his desire to prey on the Oysters. In addition to this, the dynamics or changes among the psychological structure within the poetry was also revealed. They were: ego – id – ego – superego – ego – superego – id – ego – id. The changes showed that complexity of personality structure existed despite of the illogical or absurd ideas in nonsense poetry on its surface. Character; Literature; Literary Work; Nonsense Poem; Psychoanalytic Criticism